Angiotensin-converting enzyme polymorphism and pediatric pneumonia - Nihal El Rifai; Hanan Alwakeel; Hala Shaaban; Mohamed Abdelfattah (SpringerOpen, 2018)
Objective: Pneumonia is one of the leading causes of death for the Pediatric age group under five years worldwide. The role of the angiotensin-converting enzyme (ACE) insertion/deletion (I/D) polymorphism in the risk and outcome of community-acquired pneumonia (CAP) has been studied in different ethnic populations and yielded inconsistent results. Therefore, the present study aimed to investigate whether this polymorphism is associated with the risk and outcome of CAP in the Egyptian pediatric population. Methods: The prospective observational case-control study was performed on 77 children aged 2 months to 12yrs hospitalized with CAP and 73 matched healthy controls. Candidates were subjected to clinical and radiological evaluation in addition to complete blood count, c-reactive protein and genotyping for the ACE I/D polymorphism using PCR technique. Follow up of the outcome in the form of need for oxygen, ICU admission, need for mechanical ventilation, duration of hospital stay and death was done for all patients. Results: No statistically significant differences was observed between pneumonia patients and controls regarding the different genotypes of the ACE polymorphism II, ID and DD genotypes (p = 0.773). No association was detected between the different genotypes of the ACE polymorphism II, ID and DD genotypes and the need for oxygen, ICU admission, need for mechanical ventilation, duration of hospital stay and death (P = 0.143, 0.527, 0.716, 0.288, 0.544). Conclusion: The ACE I/D polymorphism is not associated with the risk nor the outcome of pneumonia in our pediatric population. Keywords: Angiotensin-converting enzyme, Pediatric, Pneumonia, Polymorphism